Mémoire de la mémoire - Lucia Masotti (Projets de Paysage)
Following the 2010 overflowing in Italy, the newspapers’ headlines showed what was left of the “beautiful country” : a piling up of fringes juxtaposed, often without any standards, to the balance between human premises and natural settings – traditionally considered as inherent to “the beautiful landscape” of rural Italy. This contribution offers some reflections on the Italian river landscapes and the concepts used to apprehend them. Some fruitful collaborative practises between universities and public organisms may help the reconstruction of a historical memory which, at least, takes into account the latest stages of production of facilities and the feedback between the natural elements and the anthropogenic action.